De Afrikaanse Roman en de Westerse Lezer. Probleemschets en Gevalstudie - Vermeulen, Julien (Afrika Focus, 1986)
African literature, like any other literature remote in space or time, can be approached in two different ways. We can read it from our own point of view and try to appreciate it with our own literary standards. We can also try to read it as it was experienced and appreciated by its immediate audience, which means by the African public at the time of publication. Reactions given by a group of Dutch-speaking readers on a novel by E. Dongala clearly illustrate that the second approach is hardly achievable, however attractive it may seem. So we have to accept that every reading of an African literary work implies a serious degree of creative treason. KEYWORDS : Literary reception, literary criticism, African literature in French, E. Dongala